PUBLIC RELATIONS COMMUNICATION STRATEGY OF DISBUDPAREKRAF IN TOURISM PROMOTION THROUGH THE DISUMUTAJA APPLICATION - Alfridho, Mhd Adrian; Efendi, Erwan (International Journal of Cultural and Social Science, 2025)
This study aims to analyze the communication strategy of the Public Relations Division of the Department of Culture, Tourism, and Creative Economy of North Sumatra (Disbudparekraf Sumut) in promoting tourism through the DiSumutAja application. This research employs a qualitative phenomenological approach within a constructivist paradigm to understand user experiences and digital-based promotional strategies. The theoretical frameworks used are the Diffusion of Innovation Theory and Media Richness Theory to explore how this digital innovation is adopted and to evaluate the effectiveness of the communication media used. Data collection methods include semi-structured interviews with representatives from Disbudparekraf and app users, direct observation of the application's usage, and document analysis. The data were analyzed using the interactive model of Miles, Huberman, and Saldana. The findings reveal that the DiSumutAja application has become an effective communication tool in delivering integrated information on tourist destinations, culture, and local events through social media. However, the application still faces challenges regarding user interactivity, limited two-way communication features, and minimal collaboration with the private sector. In conclusion, the use of the DiSumutAja application has enhanced the visibility of North Sumatra’s tourism, but optimization is needed by incorporating user feedback features, expanding collaborative networks with the private sector, and adopting more participatory and adaptive communication approaches. With these improvements, the application is expected to become a more inclusive, responsive, and sustainable tourism promotion platform in the digital era.